EFEKTIVITAS PELAYANAN PADA KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA SAMARINDA - Marina Lisa Anggraeni (ADMINISTRASI PUBLIK, 2018)
The purpose of this research is to find out howThe Effectiveness Of The Service In Dinas Penanaman modal and pelayanan terpadu satu pintu samarinda. This Thesis research is planned for seven months i.e. November 2017 until September 2018. Research on the method of this research is a descriptive qualitative researching about The Effectiveness Of The Service In Dinas Penanaman modal and pelayanan terpadu satu pintu samarinda. Data collection with interviews, observation and documentation. Results of the study stated that The Effectiveness Of The Service In Dinas Penanaman modal and pelayanan terpadu satu pintu samarinda, The effectiveness of the Service function to find out the extent of services provided to the community and so far has been running fine and according with the standard Operational procedures (SOP) in force.